2019
DOI: 10.3390/fi11030080
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Utility and Future of Collaborative Consumption Platforms Offering Tourism Related Services

Abstract: The present study analyzes four well-known online platforms used in the tourist industry for travelling, accommodation, eating, and touring (Blablacar, Airbnb, Eatwith, and Trip4real). The objective is to analyze the utility of the portals, intentions for future use and recommendation (prospective), and reputation. The method is an experimental design with a control group and experimental group. Within both groups, three scales were applied. The results indicate clear differences between the control and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Either by appealing to socio-psychological theories, which could explain consumer behaviour and generational differences, or to others, of an economic-organisational nature, centred on the tourist product or service. Secondly, within the empirical studies, many are quantitative works of an exploratory nature (i.e., Monaco, 2018;Fondevila-Gascón et al, 2019;Del Moral-Pérez et al, 2021;Entina et al, 2021) while others try to develop causal models, especially through structural equation modelling given the difficulty of establishing causal relationships such as: Martínez-González & Álvarez-Albelo (2019).…”
Section: New Consumption Patterns In the Tourism Sector: Generation Zmentioning
confidence: 99%
“…Either by appealing to socio-psychological theories, which could explain consumer behaviour and generational differences, or to others, of an economic-organisational nature, centred on the tourist product or service. Secondly, within the empirical studies, many are quantitative works of an exploratory nature (i.e., Monaco, 2018;Fondevila-Gascón et al, 2019;Del Moral-Pérez et al, 2021;Entina et al, 2021) while others try to develop causal models, especially through structural equation modelling given the difficulty of establishing causal relationships such as: Martínez-González & Álvarez-Albelo (2019).…”
Section: New Consumption Patterns In the Tourism Sector: Generation Zmentioning
confidence: 99%
“…For example, Sun et al [19] empirically found that the impact of the effectiveness of regulation on trust in the context of social media was stronger for male consumers than for female consumers. In the context of collaborative consumption, gender differences have been investigated in various sectors, such as travel [15], [81], tourism [82], consumption of luxury products [83], and bicycle-sharing [12]. Gender differences were also validated in the influencing factors of collaborative consumption intention, such as trust [15], and sustainability motives [84].…”
Section: ) the Moderating Role Of Gendermentioning
confidence: 99%
“…The main motivations for adopting the CC approach are economic, to save and optimize resources(Barnes & Mattsson, 2016), the lower need for ownership, and the availability of new digital platforms (Fondevila‐Gascón et al, 2019). This study argues that with the popularity of smart devices, governments can develop cost‐effective and ubiquitous digital means for LIC governments to better optimize limited resources (Meiyanti et al, 2019; Singh et al, 2019; Zafiropoulos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%